Analisis Faktor yang Berhubungan dengan Penggunaan Produk Tembakau Non-Rokok pada Pelajar SMP di Indonesia - Fauzi, Ridhwan; Handari, Siti Riptifah Tri (Media Kesehatan Masyarakat Indonesia, 2019)
Non-cigarettes tobacco smoking products have similar negative impact to the health as conventional cigarettes. However, most of adolescent are unaware of the problem. Nowdays, the products gain more popularity among youth. This study aims to find out factors associated with non-cigarettes tobacco products (NCTP) use among junior high school students in Indonesia. The study used crossectional design. The source of data were secondary data of the Global Youth Tobacco Survey (GYTS) 2014. GYTS is a school-based survey of junior high school students. Data was obatianed from three regional (Jakarta, Bekasi, and medan) from September 21st 2013 to June 20th2014. The population of study is national representative of junior high school students in Indonesia. The sampling method was multistage cluster random sampling. Total sampling was 5.986 students. Data was weighted by SUDAN and analyzed by chisquare test and multiple logistic regressions. Study revealed that about 3,6% respondents ever used NCTP in past 30 days. NCTC used was significantly associated with gender, conventional cigarettes smoking status and attitude in p<0,001. Students who regularly smoked convenstional cigarettes were 12,055 (CI 95%: 7,674-18,937) more likely to use NCTP than non smoker.